PENGARUH PERBEDAAN METODE EKSTRAKSI DAUN JATI (Tectona grandis L.f) TERHADAP AKTIVITAS ANTIBAKTERI PADA Escherichia coli - Sambodo, Dwi Kurniawati; Marsel, Fransiska; Sambodo, Herlina Prasetyowati; Arlesia, Nandia (Jurnal Riset Kefarmasian Indonesia, 2022)
The use of teak is limited to wood and stems with high economic value. The part of the teak that has not been utilized optimally is the teak leaf. Teak leaves are only used traditionally as food wrappers and traditional medicines. According to several studies, Sumthong (2007) in Setyawan (2012) stated that teak leaves contain several bioactive compounds, namely tektoquinone, tannic acid, gallic acid and several other organic acids. The presence of bioactive compounds in teak leaves can also be used as an antibacterial agent. This study was conducted to determine the effect of different extraction methods maceration, percolation and microwave Microwave Assisted Extraction on the antibacterial activity of teak leaves against Escherichia coli bacteria. From the research, it can be concluded that the different extraction methods of teak (Tectona grandis L.f) leaves have a significant effect on the antibacterial activity of Escherichia coli and the microwave extraction method is effective as an antibacterial against Escherichia coli as seen from the clear zone produced which is greater than the maceration and percolation extraction methods.